2018
DOI: 10.1002/jbm.a.36395
|View full text |Cite
|
Sign up to set email alerts
|

Gelatin/nano‐hydroxyapatite hydrogel scaffold prepared by sol‐gel technology as filler to repair bone defects

Abstract: This study reports on the development of a scaffold with a gradient of bioactive solid signal embedded in the biodegradable polymer matrix by combining a sol-gel approach and freeze-drying technology. The chemical approach based on the sol-gel transition of calcium phosphates ensures the particles dispersion into the gelatin matrix and a direct control of interaction among COOH /Ca ions. Morphological analysis demonstrated that on the basis of the amount of inorganic component and by using specific process con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 61 publications
(32 citation statements)
references
References 47 publications
(53 reference statements)
0
32
0
Order By: Relevance
“…It is also possible to reinforce hydrogels with frames made from synthetic microfibers [49]. The most widespread strategies are those that improve the hydrogel properties by including secondary polymers and various nanostructures into the main hydrogel to create polycomposite hydrogel scaffolds [[50], [51], [52]]. All the above considerations indicate the topicality of developing new hydrogel scaffolds based on natural polymers and of investigations into the effects of various factors (for example, the composite structure, interaction of biopolymers, conditions of co-polymerization of components etc.)…”
Section: Introductionmentioning
confidence: 99%
“…It is also possible to reinforce hydrogels with frames made from synthetic microfibers [49]. The most widespread strategies are those that improve the hydrogel properties by including secondary polymers and various nanostructures into the main hydrogel to create polycomposite hydrogel scaffolds [[50], [51], [52]]. All the above considerations indicate the topicality of developing new hydrogel scaffolds based on natural polymers and of investigations into the effects of various factors (for example, the composite structure, interaction of biopolymers, conditions of co-polymerization of components etc.)…”
Section: Introductionmentioning
confidence: 99%
“…After 30 min of stirring, the solutions were sonicated to remove air bubbles and then poured into a Teflon mold to be processed for 48 h by freeze-drying. The crosslinking of Gelatin was performed by soaking porous lyophilized scaffolds, at different time points (1, 3, and 6 h) at room temperature, in acetone–water solution (4:1 v/v) containing a water-soluble EDC, followed by incubation at 4°C for 24 h. The scaffold/solvent volume ratio was kept at 1 wt/v%, considering our previous study (Raucci et al, 2018), in order to maintain a porous structure. Meanwhile, the amount of crosslinking agent was 0.7 wt/v% respect to volume solution of acetone-water (Raucci et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…In another study compressive modulus of gelatin HAp NPs composite hydrogel has been shown to decrease by increasing the weight percentage of HAp NPs. Such decrease was attributed to negative effect of HAp NPs on the crosslinking efficiency (Raucci et al, 2018).…”
Section: Ceramic Nanoparticlesmentioning
confidence: 99%